Inhibitory activity of Lactobacillus plantarum U10 isolated from Tempoyak (fermented durian) Made in Indonesia against Salmonella typhi - SOGANDI SOGANDI; APON ZAENAL MUSTOPA; I MADE ARTIKA; BUGI RATNO BUDIARTO (Indonesian Society for microbiology, 2015)
Lactobacillus plantarum U10 produced bacteriocin U10 which was isolated from a traditionally fermented food â€œtempoyakâ€ from Sumatera Island in Indonesia. Production of the bacteriocins started at early exponential phase and reached maximum level at early stationary phase. Furthermore, plantaricins U10 was purified by ammonium sulphate precipitation followed by gel filtration chromatography. L. plantarum U10 produced two bacteriocins with a molecular mass of approximately 4.5 and 9.8 kDa by SDS-PAGE.Â The mode of action of plantaricins U10 was identified as bactericidal agents against Salmonella typhi ATCC25241 as proven by CFU counting and SEM micrographs that showed differences in cell structures between treated cells and the non-treated control. SEM examination also confirmed structural destruction of membrane cells integrity and considerable morphological alteration of S.typhi.